Environmental taxation as an economic instrument to negative externality produced by pollution in Peru - García Malpica, Paula Denisse (2018)
The present investigation allowed to describe how environmental taxation can be applied as an economic instrument in the face of pollution, this being a negative externality. A descriptive analysis of the market failure that represents pollution was carried out, and the tax economic instrument on environmental matters was presented as an action tool, which acts first as compensation for the damage performed and second, as an incentive for behaviors that are not harmful to the environment. Likewise, the various macro figures that represent the cost of environmental degradation in Peru in terms of Gross Domestic Product, provided by the World Bank, were presented. The main environmental problems that generate the most significant economic costs were determined. In this way, it was concluded that the most affected natural resources are air and water, which consequently affect the health and general well-being, and that taxation or environmental taxation exists as an economic instrument to reduce and avoid harmful actions that threaten ourselves in short or long terms and the environment where we live.